"I had hope. I loved this city once.": A mixed methods study of hope within the context of poverty. Issue 5 (9th February 2021) - Clark, Rachael S.; Stubbeman, Bobbie L.
Abstract: The purpose of this emergent mixed methods study was to measure hope in individuals living in poverty and to explore potential contextual influences on hope. We used a sequential mixed methods study in which the quantitative phase was administered first followed by a qualitative phase. Participants in impoverished areas scored higher in hope than a comparison group of university students. In a follow‐up qualitative phase, participants named contributors to and detractors from hope that included experiences driven by environmental factors. Findings were organized according to Ecological Systems Theory (EST). Participants named factors from all levels of EST, and interactions between levels were evident. These results and findings support the inclusion of relevant contextual factors in psychological inquiry, and we suggest deliberate inclusion of individuals from all socioeconomic groups in future positive psychological research.